(untitled) (Research, Society and Development, 2020)
The present study aimed to identify the scientific evidence of interventions to promote adherence to Standard Precautions among health care workers. It is an integrative review with research of articles carried out in the databases LILACS, Scopus and MEDLINE. A time frame of the last 5 years was used in all searches. For data treatment, the classification of the levels of evidence of each study was carried out through the analysis of its research question. After applying the inclusion and exclusion criteria, 18 scientific articles that comprised the review were selected. It was identified that most strategies involved educational interventions or educational interventions with some additional strategy and that most investigations obtained favorable results when comparing educational intervention with no intervention. It is proposed to carry out intervention studies in the Brazilian scenario, with strategies planned based on international investigations, but which also consider the particularities of the reality found in national institutions.